Evaluation of a blood-free, charcoal-based, selective medium for the isolation of Campylobacter organisms from feces. - Karmali, M A (1986)
A blood-free, charcoal-based selective medium (CSM) consisting of a Columbia agar base, activated charcoal (4 g/liter), hematin (0.032 g/liter), sodium pyruvate (0.1 g/liter), cefoperazone (32 mg/liter), vancomycin (20 mg/liter), and cycloheximide (100 mg/liter) supported the growth of Campylobacter jejuni and C. coli with colony counts equivalent to those obtained on antibiotic-free horse blood agar. CSM was compared to Skirrow medium (SKM) for the recovery of C. jejuni and C. coli from stools of patients with diarrhea, the media being incubated for 2 days under reduced oxygen tension at 43 degrees C. These campylobacters were isolated from 35 (2.9%) of 1,227 stools tested (29 on both media, 5 on CSM alone, and one on SKM alone). Whenever C. jejuni and C. coli were recovered, growth was pure on 29 CSM cultures (85%), but on only 11 SKM cultures (37%). Complete suppression of "contaminating" flora occurred in 704 CSM cultures (57%) compared with 426 SKM cultures (35%). CSM more effectively suppressed contaminating pseudomonads, gram-positive organisms, and yeasts than did SKM; both media failed to suppress members of the family Enterobacteriaceae in about a quarter of the samples. Studies on 20 representative Enterobacteriaceae contaminants showed that susceptibility to cefoperazone and growth on CSM were markedly dependent on inoculum size; 12 strains were inhibited by cefoperazone (32 mg/liter) at inoculum sizes of 5 X 10(2) and 5 X 10(4) but not 5 X 10(6) organisms, indicating that the frequency of contaminants on CSM could probably be reduced further by ensuring that stools were not inoculated too heavily on CSM. Our findings confirm that charcoal is an effective substitute for blood in media for growing campylobacters, and that CSM is a highly effective blood-free selective medium for isolating C. jejuni and C. coli from stools.